(untitled) (Journal of Enam Medical College, 2016)
A 60-year-old man was diagnosed as a case of malignant melanoma on the left sole and received three cycles of neoadjuvant chemotherapy. Then local excision of the lesion was done. During preoperative diagnostic work-up, there were no features of metastases in lung, liver and bones. On the 3rd postoperative day he presented with right sided hemiparesis. After appearance of neurological features, computed tomography was done and it showed multiple cerebral metastases surrounded by brain edema in both the parietal lobes. The lesions were large, causing increased intracranial pressure. The patient was then referred to the National Institute of Neuroscience (NINS) for further management. J Enam Med Col 2016; 6(1): 51-54